2022
DOI: 10.1186/s12913-022-08819-0
|View full text |Cite
|
Sign up to set email alerts
|

Economic Burden of Diabetic Mellitus Among Patients on Follow-up Care in Hospitals of Southwest Shewa Zone, Central Ethiopia

Abstract: Background Diabetes has emerged as one of the most serious health issues of the twenty-first century. Diabetes and its complications expose individuals and their families to catastrophic healthcare costs, which have a severe impact on the country's economy. Though the prevalence of diabetes is rising quicker in Ethiopia, little is known about its economic impact. Hence, this study aimed to determine the total cost of diabetic mellitus and associated factors among patients attending hospitals in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 41 publications
(51 reference statements)
0
10
0
Order By: Relevance
“…A recent study on the financial impact of diabetes revealed that diabetic care costs US $ 38.23 per month, which is more than a significant portion of the Ethiopian population earns on a monthly basis. 102 Therefore, socio-economic empowerment of patients could be vital to trim the burden of DM in Ethiopia.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study on the financial impact of diabetes revealed that diabetic care costs US $ 38.23 per month, which is more than a significant portion of the Ethiopian population earns on a monthly basis. 102 Therefore, socio-economic empowerment of patients could be vital to trim the burden of DM in Ethiopia.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, hospital-acquired and ventilator-associated pneumonia cases that required intensive care have been found to have increased hospitalization time and costs 21,22 . The impact of development of DM and infectious complications in DM patients on hospitalization costs has also been frequently reported [23][24][25] . In other studies, oral bacterial infection and poor oral health were shown to be risk factors related to surgical site infection after various cancer and cardiovascular surgical procedures 9,[26][27][28][29] , while a relationship between oral microbial colonization and ventilator-associated pneumonia in patients in intensive care units has also been reported 30,31 .…”
Section: Discussionmentioning
confidence: 99%
“…When EMs remain unaffordable, patients may forgo their treatment especially if they are paying out-of-pocket for their medicines, which increases the burden of DM and its complications [ 38 ]. The findings from an economic study in the same region has reported as to how the medicines cost constitute a high portion from the total cost of diabetes, which has implications both at the individual patients and societal levels [ 39 ]. In order to enhance access to EMs and protect citizens from the devastating diabetes complications and financial risk that have huge effect on public health, the country should work to make health care financing sustainable for its efficient operation.…”
Section: Discussionmentioning
confidence: 99%